L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

État de lieu des données internationales sur les inégalités de genre dans le développement international - Machkouri, Zora Ait El; Bourassa-Dansereau, Caterine; Langevin, Marie (Observatoire francophone pour le développement inclusif par le genre, 2022)
Ce cahier présente un premier état des lieux du développement inclusif par le genre (DIG) et brosse le portrait des sources de données internationales et institutionnelles existantes et accessibles au sujet du développement inclusif afin d’outiller l’Observatoire et de soutenir ses partenaires dans leur volonté de se saisir de cette problématique de l’égalité et de participer concrètement aux défis qui en découlent. En répertoriant les sources de données existantes, en analysant leurs caractéristiques et leurs lacunes ainsi qu’en identifiant les angles morts dans la couverture des dimensions inégalitaires persistantes au sein des secteurs clés du DIG (milieux économiques, systèmes éducatifs, domaine de l’enseignement supérieur et de la recherche ), nous cernons des enjeux qui sont au cœur de la mission de l’Observatoire.
Keywords: 2000 à aujourd'hui; OFDIG; afrique; amériques; approches et analyses; discipline; développement durable; empowerment; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; statistiques; systèmes d'oppressions; thématiques

Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual health studies in gay and lesbian people: A critical review of the literature - Mijas, Magdalena; Grabski, Bartosz; Blukacz, Mateusz; Davies, London, UK, Dominic Pink Therapy (The Journal of Sexual Medicine, 2021)
Arrière-plan Le sujet de la santé sexuelle des gays et des lesbiennes semble être très peu étudié, au moins en partie en raison des limites générales inhérentes aux études sur la sexualité ainsi que des préjugés hétéronormatifs et des difficultés à atteindre ces populations. But Examiner de manière critique les études sur la santé sexuelle des gais et des lesbiennes afin d'identifier les lacunes et les préjugés existants dans la portée et la construction générale des recherches publiées. Méthodes L'ensemble de données comprenait 556 articles évalués par des pairs et identifiés grâce à la recherche Medline. Les caractéristiques clés des études ont été extraites selon le livre de codes développé pour cette étude et analysées de manière descriptive. Résultats Les résultats comprenaient : la méthodologie de recherche, la conception de l’étude, l’échantillonnage, le sujet de recherche et l’inclusion de la diversité dans les populations étudiées. Résultats La majorité des études étaient quantitatives (70,5 %), transversales (83,6 %) et utilisaient un échantillonnage de commodité (83,2 %). La plupart des articles portaient sur les comportements à risque en matière de VIH/IST, les vulnérabilités et la gestion des risques (26,3 %). Le sujet le moins souvent abordé concernait la fonction sexuelle des participants gais et lesbiennes plus âgés (0,5 %). Plus de 68 % des articles s'appuyaient sur des échantillons masculins et les études portant sur des échantillons exclusivement féminins en représentaient moins de 13 %. La plupart des études n'ont pas recruté de groupe d'âge spécifique (77,7 %) et incluaient des informations sur l'origine ethnique des participants à l'étude (62 %). Les informations sur l'éducation (58,7 %) ou d'autres indicateurs du statut socio-économique (52,8 %) étaient moins souvent déclarées. Traduction clinique Les limites méthodologiques des conceptions d'étude actuelles, des procédures d'échantillonnage et de la composition des échantillons, ainsi que de nombreuses zones d'omission limitent l'utilité clinique des recherches existantes. Points forts et Limites Cette étude offre un aperçu critique des défis les plus importants associés aux études sur la santé sexuelle des gais et des lesbiennes. La recherche dans la base de données Medline uniquement, l'inclusion exclusive d'articles rédigés en anglais et la portée limitée (sexualité gay et lesbienne uniquement) de la revue constituent les limites les plus importantes. Conclusions La santé sexuelle des gays et des lesbiennes est un domaine peu étudié, caractérisé par une concentration principale sur le VIH/IST et un manque de recherche de meilleure qualité incluant diverses sous-populations.
Keywords: approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; médecine; personnes gay; personnes lesbiennes; ressource en ligne; revue de la littérature; santé; santé sexuelle; sciences; systèmes d'oppressions; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (The MIT Press, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics–one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres